Analisis Kepercayaan dan Kualitas Situs pada Minat Beli Produk E-Commerce Bukalapak - Ani Solihat; Hana Friska Tampubolon; Rani Rahmayani; Andry Trijumansyah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
The purpose of this study is to examine the effects of consumer trust and website quality on purchase intention in Bukalapak e-commerce platform. Data were collected through questionnaires distributed online by means of Google Forms. 100 sample respondents were selected purposively. The sample criterion is having an experience of buying products from Bukalapak at least once. The results of data analysis revealed that consumer trust and website quality had significant positive influence on purchase intention both partially and simultaneously.